Recurrence of Congenital Diaphragmatic Hernia: Risk Factors, Management, and Future Perspectives - Macchini, Francesco; Raffaeli, Genny; Amodeo, Ilaria; Ichino, Martina; Encinas, José Luis; Martinez, Leopoldo; Wessel, Lucas; Cavallaro, Giacomo (Frontiers in Pediatrics, 2022)
Recurrence is one of the most common surgical complications in Congenital Diaphragmatic Hernia (CDH). It could remain clinically silent for a long time or present as an acute complication week, months, or even years after the primary surgery. Several risk factors have been identified so far. An extended diaphragmatic defect represents one of the leading independent risk factors, together with indirect signs of large defect such as the liver position related to the diaphragm and the use of the prosthetic patch and with the use of a minimally invasive surgical (MIS) approach. However, the exact contribution of each factor and the overall risk of recurrence during the life span still need to be fully understood. This mini-review aims to give an overview of the current knowledge regarding CDH recurrence, focusing on predisposing factors, clinical presentation, management and follow-up of high-risk patients, and future perspectives.